MODERN CLASSIFICATIONS OF RESERVES AND RESOURCES APPLICATION IN EVALUATING DOMESTIC DEPOSITS OF BENTONITIC CLAYS - Andreeva, O.; Kurylo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The systematization and analysis of geological study of objects of bentonitic raw-material bases with using classifications largest reserves, the quality and technological properties, the degree of geological and technical-economic study were carried out.